2013
DOI: 10.1016/j.nbd.2013.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Glial A30P alpha-synuclein pathology segregates neurogenesis from anxiety-related behavior in conditional transgenic mice

Abstract: In Parkinson’s disease (PD) patients, alpha-synuclein (α-syn) pathology advances in form of Lewy bodies and Lewy neurites throughout the brain. Clinically, PD is defined by motor symptoms that are predominantly attributed to the dopaminergic cell loss in the substantia nigra. However, motor deficits are frequently preceded by smell deficiency or neuropsychological symptoms, including increased anxiety and cognitive dysfunction. Accumulating evidence indicates that aggregation of α-syn impairs synaptic function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 94 publications
2
29
0
Order By: Relevance
“…Neuropsychiatric disorders, such as depression, anxiety and cognitive impairment can respond to dopaminergic therapy (Chaudhuri and Schapira, 2009). Hippocampal adult neurogenesis was recently studied in animal models (Hinkle et al, 2012;Kohl et al, 2012;Marxreiter et al, 2013) and in PD patients (Höglinger et al, 2004), linking adult neurogenesis to depression-like behavior and cognitive dysfunction in PD. In addition, dysfunction of the catecholaminergic system in the limbic system seems to be related to the symptom of depression (Remy et al, 2005), which responds to dopaminergic therapy with L-DOPA and/or PPX (Barone et al, 2010;Rektorova et al, 2005).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropsychiatric disorders, such as depression, anxiety and cognitive impairment can respond to dopaminergic therapy (Chaudhuri and Schapira, 2009). Hippocampal adult neurogenesis was recently studied in animal models (Hinkle et al, 2012;Kohl et al, 2012;Marxreiter et al, 2013) and in PD patients (Höglinger et al, 2004), linking adult neurogenesis to depression-like behavior and cognitive dysfunction in PD. In addition, dysfunction of the catecholaminergic system in the limbic system seems to be related to the symptom of depression (Remy et al, 2005), which responds to dopaminergic therapy with L-DOPA and/or PPX (Barone et al, 2010;Rektorova et al, 2005).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In a post-mortem study of PD patients, a decreased number of neural progenitor cells in the dentate gyrus and the OB has been found, suggesting a downregulation of neurogenesis in both neurogenic regions (Höglinger et al, 2004). In transgenic animal models of PD, the number of adult-born neurons was decreased in the dentate gyrus (Crews et al, 2008;Marxreiter et al, 2013;Nuber et al, 2008) and a dysregulation of mood was reported (Marxreiter et al, 2013). In rodent toxin-induced models of PD, the results are inconsistent, for example, a decreased (Suzuki et al, 2010) or unchanged proliferation (Winner et al, 2009) was reported in the SGZ in a 6-hydroxydopamine (6-OHDA) rat model of PD; in a mouse model of 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridin (MPTP), adult M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
“…However, in the OB, the amount of newly generated DA neurons is decreased in the mutant mice. More recently, the same group investigated the effect of the mutation on hippocampus plasticity and found that the survival of new hippocampal neurons is dramatically decreased in these mice [176]. The cause of this decrease in newly formed neurons has not been investigated in this model.…”
Section: Snca (Park1/park4)mentioning
confidence: 99%
“…The Nse is a cytoplasmatic glycolytic enzyme, an increase of whose levels is considered as a sensitive marker of neuronal damage (Schaf et al, 2005; Al-Jarrah and Jamous, 2011). Age-dependent and site-specific increase in co-localization of α-synuclein and S100b have been observed within astrocytes (Marxreiter et al, 2013). Parkinsonism also increases the expressions of Nse and S100b (Al-Jarrah and Jamous, 2011).…”
Section: Discussionmentioning
confidence: 99%